2015
DOI: 10.1007/s10238-015-0352-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased B7H4 tissue expression correlates with high CA19.9 serum levels and a worse prognosis of pancreatic adenocarcinoma

Abstract: Pancreatic cancer (PC) is a leading cause of cancer death worldwide, especially in Western societies. Its aggressive nature and poor prognosis increase the need for identifying new and more accurate diagnostic and prognostic tools. We studied 41 patients who had undergone radical surgical resection for PC, investigated B7H4 protein expression in the PC tissue specimens of these patients by immunohistochemistry and analyzed several clinical and pathological features. The positive expression of the B7H4 antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It has been suggested that B7-H4 be included in panels of markers involved in cancer stem cell maintenance [18]. In pancreatic cancer, B7-H4 was a negative prognostic marker, indicating more resistance to chemotherapy with gemcitabine [19]. In breast cancer, B7-H4 was highly expressed in both breast cancer and stroma cells, independently of the intrinsic subtypes of breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that B7-H4 be included in panels of markers involved in cancer stem cell maintenance [18]. In pancreatic cancer, B7-H4 was a negative prognostic marker, indicating more resistance to chemotherapy with gemcitabine [19]. In breast cancer, B7-H4 was highly expressed in both breast cancer and stroma cells, independently of the intrinsic subtypes of breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Manual review of the reference lists of retrieved manuscripts concerning B7H1 or B7H4 expression in pancreatic cancer yielded four additional studies that met the inclusion criteria for this meta-analysis. However, 16 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were finally selected for metaanalysis after the removal of duplicates and the application of eligibility criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The studies were published between 2007 and 2023. They consisted of the following cancer types: OS-osteosarcoma [27], Pca-prostate cancer [28,29], CvC-cervical cancer [30,31], CCA-cholangiocarcinoma [13,32], PDAC-pancreatic ductal adenocarcinoma [33][34][35][36], UCC-urothelial cell carcinoma [36], HNSCC-head and neck squamous cell carcinoma [37,38], OC-ovarian cancer [39], ESCC-esophageal squamous cell carcinoma [28,40], BC-breast cancer [41,42], GC-gastric cancer [43,44], ECC-endometrial cancer [45], NSCLC-non-squamous cell lung carcinoma [46,47], RCC-renal cell carcinoma [48], and CRC-colorectal cancer [39,[49][50][51][52]. The sample sizes ranged from 37 to 996, with a total of 6357 patients.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%